SIMULASI ALIRAN DAYA PADA PEMBANGKIT LISTRIK TENAGA MESIN GAS (PLTMG) BADAS UNTUK SISTEM KELISTRIKAN SUMBAWA BESAR MENGGUNAKAN SOFTWARE ETAP 16 - Indra Darmawan; Fuad Abdurrahman Rafif; Addien Wahyu Wiratama (Jurnal Informatika Teknologi dan Sains, 2019)
Electric power system is a process of electrical energy generation to dispense to users. A well-integrated system provides quality assurance for system reliability. Analysis is conducted to minimize dispensing losses. The electrical system of Sumbawa Besar is currently in the process of upgrading 150 KV transmission distribution capacity with PLTMG BADAS as the largest generation center. The research was conducted by analyzing the power flow on PLTMG BADAS for the electrical system of Sumbawa Besar which was reviewed on 20 KV bus system, and by simulating using ETAP 16 software . The research method is done with data derived from Sumbawa's PLN and analysis of the power flow calculation using the method Newton-Raphson precision value 0.0001. The simulation is performed on three generation scenarios, namely: 1) Operation 1 PLTMG engine, 2) operation 2 PLTMG engines, 3) operation of the entire PLTMG machine. All three scenarios are done under normal operating conditions. Simulated results show that the analysis of power flows by Newton-Raphson method generates 2 iterations in each scenario, and the following parameters are obtained: 1) average of the highest voltage value in Scenario 1 OF 20.43 KV With phase angle-14.3, 2) Total active power – highest reactive in Scenario 2 of 44.475 MW and 9.557 MVAR, 3) Scenario 1 has the lowest power loss of 2.634 MW and 5.168 MVAR and voltage fall by 2.275%.